Research on variations and the validity of the proverbs collected by Fernan Caballero - M. Jarilla Bravo, Salud (Romanica Olomucensia, 2024)
As time passes by, speakers' paremiological competence diminishes and breaks down. Proverbs gradually lose their relevance and adapt to new needs and linguistic changes; they undergo variations that move them away from their more classical form, facilitating their adaptation to new times and, above all, to lexical evolution. The translator who searches for paremias in old repertoires is sometimes unable to locate the possible variants of the form. This can lead the translator to make the mistake of thinking that it is a de-automatisation carried out with a specific function by the literary author. This research aims to locate the possible variations that some of the proverbs collected by Fernan Caballero, the nom de plume of Cecilia Bohl de Faber y Ruiz de Larrea, have undergone with the passage of time. The sententious statements inserted in her works do not come from dictionaries or proverbs but from informants, as the writer, impressed by the richness of Andalusian folklore, devoted herself to collecting these samples of popular wisdom. Fieldwork was carried out with informants in the South of Spain, where Fernan Caballero worked, with the aim of studying and analysing the variations or modifications that the paremias have undergone over time. This qualitative study based on personal interviews provides us with a sample of the possible state of such paremias in the present. Among the most notable findings was a considerable loss of paremiological competence, as the number of paremias that are recognised and used has declined considerably.
Keywords: proverbs; variation; paremiology; paremiography; Fernan Caballero